2006
DOI: 10.1139/s05-044
|View full text |Cite
|
Sign up to set email alerts
|

A targeted study on possible free ammonia inhibition of Nitrospira

Abstract: Batch tests were carried out with Nitrospira in mixed and pure cultures using concentrations of free ammonia widely believed to be inhibitory to nitrite-oxidizing organisms. The mixed culture batch tests were conducted with mixed liquor from a bench scale completely stirred tank reactor (CSTR) treating a synthetic wastewater having a low C:N ratio. Nitrospira were confirmed as the dominant nitrite oxidizers via RNA slot blotting. Nitrospira moscoviensis were used for the pure culture trials. The results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Meanwhile, a higher nitrite accumulation in the experimental reactor indicated that FA treatment in phase II (130.6 mg NH 3 L −1 ) could inhibit the activity of Nitrospira , not contradictory with the previous study, where an FA concentration of 12.1 mg NH 3 L −1 was ineffective in the inhibition of Nitrospira . 36 Because the FA concentration in the side-stream sludge treatment was nearly eleven times higher than that in the literature, Nitrolancea was not favored at the operational conditions of this study for its thermophilic ecological niche. The relative abundance of Nitrospira increased to 0.5% in C3 and 0.7% in E3.…”
Section: Resultsmentioning
confidence: 73%
“…Meanwhile, a higher nitrite accumulation in the experimental reactor indicated that FA treatment in phase II (130.6 mg NH 3 L −1 ) could inhibit the activity of Nitrospira , not contradictory with the previous study, where an FA concentration of 12.1 mg NH 3 L −1 was ineffective in the inhibition of Nitrospira . 36 Because the FA concentration in the side-stream sludge treatment was nearly eleven times higher than that in the literature, Nitrolancea was not favored at the operational conditions of this study for its thermophilic ecological niche. The relative abundance of Nitrospira increased to 0.5% in C3 and 0.7% in E3.…”
Section: Resultsmentioning
confidence: 73%
“…A particular sensitivity of NOB towards FA was stated elsewhere (Villaverde et al ., 2000; Kim et al ., 2006). However, this issue seems to be controversial, since authors recently reported relatively high FA tolerances for Nitrospira (mixed and pure cultures) and Nitrobacter (Simm et al ., 2006; Hawkins et al ., 2010). These are in accordance with the results in this study, where approximate 0.7 mM NH 3 ‐N did not inhibit growth of Ecomares 2.1.…”
Section: Discussionmentioning
confidence: 99%
“…The washout of NOB and promotion of shortcut nitrogen removal can provide up to 25% aeration energy savings compared to conventional nitrification–denitrification processes, or 60% aeration savings when combined with anammox . Consequently, much focus has been placed on developing operational selective pressures for AS that wash out NOB by means of dissolved oxygen limitation, , cyclic aeration, , solids retention time (SRT) control, or exposure of biomass to inhibitory agents like free ammonia (FA) and free nitrous acid. , However, NOB have been shown to adapt to many of these selective pressures, likely due to their high metabolic flexibility and physiological diversity, especially in Nitrospira -related genera , ( e.g. , Nitrospira _A, Nitrospira _C, Nitrospira _D, Nitrospira ,_E, and Nitrospira _F in the Genome Taxonomy Database).…”
Section: Introductionmentioning
confidence: 99%